2015
DOI: 10.1038/nphys3348
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical accretion disks in ultraluminous X-ray sources and SS 433

Abstract: Most ultraluminous X-ray sources (ULXs) are thought to be supercritical accreting compact objects, where massive outflows are inevitable. Using the long-term monitoring data with the Swift X-ray Telescope, we identified a common feature in bright, hard ULXs: they display a quasi-periodic modulation in their hard X-ray band but not in their soft band. As a result, some sources show a bimodal distribution on the hardness intensity map. We argue that these model-independent results can be well interpreted in a pi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
120
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(128 citation statements)
references
References 20 publications
6
120
1
1
Order By: Relevance
“…Spectral/flux variation in ULXs that could be explained by the clumpy disk winds has been observed on various wavelengths and timescales, such as X-ray flux on a timescale of several tens of seconds (Middleton et al 2011) and optical emission lines on 1 day timescales (Fabrika et al 2015). As pointed out by Uttley & Klein-Wolt (2015), the clumpiness of the wind may contribute to the observed evolution of high-frequency variability in GRO J1655 −40.…”
Section: Implications For Disk Winds In Other Luminous X-ray Binariesmentioning
confidence: 96%
See 1 more Smart Citation
“…Spectral/flux variation in ULXs that could be explained by the clumpy disk winds has been observed on various wavelengths and timescales, such as X-ray flux on a timescale of several tens of seconds (Middleton et al 2011) and optical emission lines on 1 day timescales (Fabrika et al 2015). As pointed out by Uttley & Klein-Wolt (2015), the clumpiness of the wind may contribute to the observed evolution of high-frequency variability in GRO J1655 −40.…”
Section: Implications For Disk Winds In Other Luminous X-ray Binariesmentioning
confidence: 96%
“…Although the ionized Fe-K absorption lines like those observed in Galactic BH binaries have never been observed in ultraluminous X-ray sources (ULXs; Walton et al 2012Walton et al , 2013, Middleton et al (2014) argued that uneven spectral structures often seen at »1 keV could be explained by broad blueshifted absorption lines. Recent deep optical spectroscopy revealed that the broad emission lines of H and He observed in ULXs (and also SS 433, which is the only known Galactic X-ray binary thought to power persistent supercritical accretion; see Fabrika 2004 and references therein) likely originate in dense, strong winds launched on supercritical accretion disks (Fabrika et al 2015). 7 Moreover, Gladstone et al (2009) suggest that massive optically thick winds could be the origin of the soft Comptonization component usually detected in ULXs.…”
Section: Implications For Disk Winds In Other Luminous X-ray Binariesmentioning
confidence: 99%
“…Fabrika et al (2015) have found that the ULX optical counterparts have very hot winds resembling WNL-type stars and their optical spectra are also very similar to that of SS 433. Using simple relations for the supercritical discs, they found that the optical luminosity of such discs is LV ∝Ṁ 9/4 0 because the stronger wind will reprocess more radiation emerging in the disc funnel.…”
Section: Discussionmentioning
confidence: 85%
“…It was suggested from X-ray and optical data (Sutton, Roberts, & Middleton 2013;Fabrika et al 2015) that ULXs are super-Eddington sources with stellar-mass black holes. If in standard accretion discs, the total luminosity is scaled with the mass accretion rate as L ∝Ṁ0, in the supercritical discs, it depends on black hole mass and is nearly independent of mass accretion rate, L ∝ L Edd (1 + a ln(Ṁ0/Ṁ Edd )), where L Edd ≈ 1.5 × 10 39 m10 erg s −1 is the Eddington luminosity, andṀ Edd corresponding mass accretion rate, m10 is a black hole mass expressed in 10M⊙, and a ∼ 0.5 − 0.7 is the parameter accounting for advection (Poutanen et al 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation